Improved pulse schemes for separated local field spectroscopy for static and spinning samples - Das, Bibhuti B.; Ajithkumar, Thalasseril G.; Ramanathan, K. V. (Solid State Nuclear Magnetic Resonance, 2008)
An improved pulse sequence for SLF experiments based on the magic sandwich (MS) scheme for homonuclear dipolar decoupling is proposed. The sequence incorporates a double MS, both on I and S spins and has been named as EXE-MS2. The proposed scheme which has a scaling factor of 1 is observed to be free from low intensity artifacts and provides better line-widths particularly for S spins labeled at multiple sites. The pulse sequence which has been applied on static oriented samples incorporates the EXE scheme where direct polarization of the S spin in the B-0 field is utilized in the place of polarization inversion and is observed to perform well without any loss of sensitivity while ensuring considerable reduction in rf power input into the sample. The EXE scheme has also been tested for solid samples under MAS. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: magic sandwich pulses; PISEMA; SLF

Immobilization of phosphotungstic acid (PTA) on imidazole functionalized silica: evidence for the nature of PTA binding by solid state NMR and reaction studies - Sofia, L. T. Aany; Krishnan, Asha; Sankar, M.; Raj, N. K. Kala; Manikandan, Palanichamy; Rajamohanan, P. R.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry C, 2009)
Phosphotungstic acid (PTA) immobilized onto imidazole functionalized fumed silica and was used its an efficient catalyst for epoxidation of a variety of olefins using aqueous H(2)O(2) as all oxidant. Negligible leaching of PTA under the reaction conditions employed indicates a strong interaction between PTA and imidazole The immobilized catalysts Could be separated and reused after the catalytic cycle Evidence for the heterogenization of PTA oil the imidazole functionalized fumed silica has been inferred from different spectroscopic techniques like IR, UV-vis, and NMR. Importantly, the nature of binding of PTA oil the support has been studied in detail by solid state NMR spectroscopy using (15)N labeled imidazole Support. It is clear from the NMR Studies that the effective heterogenization of PTA is mainly due to imidazolium ion Formation oil the support by the acidic protons of PTA and the resultant ion pair

Identification of the Zn substitution sites in La-Zn substituted SrAl12O19 from Al-27 solid-state NMR studies - Baby, Bindhu; Dey, Krishna K.; Ajithkumar, Thalasseril G.; Joy, Pattayil A. (Journal of the American Ceramic Society, 2014)
The La-Zn substituted hexagonal strontium aluminate, Sr1-xLaxAl12-xZnxO19, with the magnetoplumbite structure and having five different coordination environments for Al with different symmetries, is investigated using Al-27 solid-state NMR to get detailed information on the sites of substitution of Zn and the associated changes in the local coordination environments of Al. The objective of the study was to get information on the local structural variations in the isostructural La-Co substituted strontium ferrite, Sr1-xLaxFe12-xCoxO19, showing enhanced magnetic performance on substitution. The NMR studies on the aluminate give direct evidence for the sites of substitution and the changes in the local coordination environments. It is found that Zn is substituted at the 2a and 4f(2) AlO6 octahedral sites. However, an interesting observation from the NMR studies is the stabilization of the Al site occupancy at the penta-coordinated 2b site over the distorted tetrahedral 4eAl site, without any substitution at these sites. Large changes in the quadrupolar coupling constant of the 2a and 4e sites are observed between x=0.2 and 0.3, corresponding to the compositional region showing higher performance in the case of Sr1-xLaxFe12-xCoxO19, indicating the role of distortion of local coordination environments on suitable substitution in controlling the performance parameters.

Investigations into variations in local cationic environment in layered oxide series InGaO3(ZnO)(m) (m=1-4) - Narendranath, Soumya B.; Yadav, Ashok Kumar; Ajithkumar, Thalasseril G.; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Dey, Krishna K.; Raja, Thirumalaiswamy; Devi, R. Nandini (Dalton Transactions, 2014)
Layered oxides of the series InGaO3(ZnO)(m) (m = 1-4) are interesting due to their structural anisotropy. Here, we report a comprehensive study of their structural details, focusing on the local cationic environment in bulk powder samples by MASNMR and EXAFS, which is hitherto not attempted. It is found that the Ga geometry varies gradually from pure pentacoordinated to a mixture of penta and tetracoordinated with increasing amounts of tetracoordination as we move across the series, contrary to previous reports suggesting exclusively trigonal bipyramidal coordination in all the compounds. A similar observation is also made in the case of Zn and structural evolution involving the dissolution of Ga in a ZnO4 tetrahedral network in a sandwich layer can be discerned, as the insulating ZnO layer size increases.

Insights into the molecular dynamics in polysulfone polymers from C-13 solid-state NMR experiments - Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Anto, Ralf; Bulakh, Neelima N.; Lele, Ashish K.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry B, 2015)
The molecular and segmental motions in three different grades of ductile polysulfone polymers; poly(ether sulfone) (PESU), polysulfone (PSU), and poly(phenyl sulfone) (PPSU) are probed using C-13 solid-state NMR experiments. Polarization inversion spin exchange at magic angle (PISEMA) experiments indicates that the phenyl rings in the polymers are undergoing pi-flip motions on the order of 100 kHz. The temperature dependent PISEMA experiments show that the fraction of mobile regions that undergoes aromatic pi-flips is higher in PPSU than in the other two polymers. The center band only detection of exchange (CODEX) experiments was carried out and was unable to detect any slow segmental motions in the chains. A combination of C-13 spin-lattice relaxation time (T-1) and T-1-filtered PISEMA experiments show that the mobile regions in all the polymers are dynamically heterogeneous.

Ionic conductivity of Na3Al2P3O12 glass electrolytes role of charge compensators - Keshri, Shweta R.; Ganisetti, Sudheer; Kumar, Rajesh; Gaddam, Anuraag; Illath, Kavya; Ajithkumar, Thalasseril G.; Balaji, Sathravada; Annapurna, K.; Nasani, Narendar; Krishnan, N. M. Anoop; Allu, Amarnath R. (Inorganic Chemistry, 2021)
In glasses, a sodium ion (Na+) is a significant mobile cation that takes up a dual role, that is, as a charge compensator and also as a network modifier. As a network modifier, Na+ cations modify the structural distributions and create nonbridging oxygens. As a charge compensator, Na+ cations provide imbalanced charge for oxygen that is linked between two network-forming tetrahedra. However, the factors controlling the mobility of Na+ ions in glasses, which in turn affects the ionic conductivity, remain unclear. In the current work, using high-fidelity experiments and atomistic simulations, we demonstrate that the ionic conductivity of the Na3Al2P3O12 (Si0) glass material is dependent not only on the concentration of Na+ charge carriers but also on the number of charge-compensated oxygens within its first coordination sphere. To investigate, we chose a series of glasses formulated by the substitution of Si for P in Si0 glass based on the hypothesis that Si substitution in the presence of Na+ cations increases the number of SiOAl bonds, which enhances the role of Na as a charge compensator. The structural and conductivity properties of bulk glass materials are evaluated by molecular dynamics (MD) simulations, magic angle spinning-nuclear magnetic resonance, Raman spectroscopy, and impedance spectroscopy. We observe that the increasing number of charge-imbalanced bridging oxygens (BOs) with the substitution of Si for P in Si0 glass enhances the ionic conductivity by an order of magnitudefrom 3.7 x 10(-8) S.cm(-1) to 3.3 x 10(7) S.cm(-1) at 100 degrees C. By rigorously quantifying the channel regions in the glass structure, using MD simulations, we demonstrate that the enhanced ionic conductivity can be attributed to the increased connectivity of Na-rich channels because of the increased charge-compensated BOs around the Na atoms. Overall, this study provides new insights for designing next-generation glass-based electrolytes with superior ionic conductivity for Na-ion batteries